Enhancing Life Science Skills in Early Childhood Through Culturally Relevant Project-Based Learning: A Quasi-Experimental Study - Ramadhani, Nurhidayah; Intisari; Nur Alim Amri; Akib, Tasrif; Hajerah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Project-Based Learning (PJBL) has gained recognition as an effective pedagogical approach for fostering active learning, scientific literacy, and problem-solving skills in early childhood education. However, empirical studies on its application in culturally relevant contexts remain limited. This study examines the effectiveness of PJBL in developing life science skills among children aged 5–6 years through the